‘Ons’ en ‘hulle’: ’n ondersoek na kultuurstereotipering in ’n Vlaamse moedertaal-taalhandboek reeks, Markant - Engelbrecht, Alta (Acta Academica: Critical views on society, culture and politics, 2012)
Over the past few decades the issue of textbooks and their relevance to society has dominated the international educational reform debate. This article aims to determine the extent to which a Flemish language textbook series fosters cultural stereotyping of the ‘other’. It explains the development of diversity perspectives pertaining to textbook representation in recent years in Flanders. Huckin’s critical discourse analysis strategy, combined with the thematic analysis of Braun and Clarke are used to investigate the visual material. The findings are presented as indicators derived from the critical thematic analysis.